Regional information centers as a way of elimination the information inequality - Yadrova, G.V. (Кримський науковий центр НАН України і МОН України, 2005)
Исследована роль регионального информационного центра в создании Национальной электронной библиотеки Украины. Особое внимание уделено организации всеобщего доступа к использованию общенационального научного ресурса в учреждениях образования Крыма. Досліджена роль регіонального інформаційного центру в створенні Національної електронної бібліотеки України. Особлива увага надана організації загального доступу до використовування загальнонаціонального наукового ресурсу в установах освіти Криму. The role of regional information center in creation the national electronic library of Ukraine is explored. The special attention is given to the organization of universal access to using the national scientific resource by the Crimean educational establishments.